2008
DOI: 10.1017/s1751731107001383
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exogenous melatonin on the ovary, the embryo and the establishment of pregnancy in sheep

Abstract: Administration of melatonin to advance the breeding season in sheep has been widely used, since this hormone conveys the photoperiodic signal to the reproductive neuroendocrine axis. An increased lambing percentage has been reported following such treatment during anoestrus, which could be mediated through a higher rate of embryonic survival, either by an improvement in luteal function or by a reduction in the antiluteolytic mechanisms. The aim of this article is to review the body of knowledge on the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…Stenbak et al (2001) reported that the fertilization rates of oocytes recovered from superovulated ewes were higher in the reproductive season than they were in anestrus. A previous study of our group demonstrated that treatment with exogenous melatonin at lambing improves the viability of ovine embryos from undernourished ewes during the anoestrous period, although the effects of exogenous melatonin on the ovary and early embryos remain unclear (Abecia et al, 2008;Vázquez et al, 2010b).…”
Section: Introductionmentioning
confidence: 90%
“…Stenbak et al (2001) reported that the fertilization rates of oocytes recovered from superovulated ewes were higher in the reproductive season than they were in anestrus. A previous study of our group demonstrated that treatment with exogenous melatonin at lambing improves the viability of ovine embryos from undernourished ewes during the anoestrous period, although the effects of exogenous melatonin on the ovary and early embryos remain unclear (Abecia et al, 2008;Vázquez et al, 2010b).…”
Section: Introductionmentioning
confidence: 90%
“…Those effects are associated with an improvement in ovulation rate , luteal function (Durotoye et al, 1997;Abecia et al, 2002) and embryo viability (Forcada et al, 2006). For a summary of the effects of exogenous melatonin on the ovary and early embryos in ewes, see Abecia et al (2008). The high amphilicity of melatonin promotes its rapid transfer into organs and fluids, and this pineal hormone can rapidly pass through cellular membranes.…”
mentioning
confidence: 99%
“…Role of melatonin in the regulation of the circadian and annual rhythm has been exploited to modulate ovarian activities in seasonal species such as sheep (Abecia et al. ), goat (Kumar and Purohit ) and mare (McManus and Fitzgerald ); this investigation points to similar role of this hormone in buffalo reproduction.…”
Section: Discussionmentioning
confidence: 65%